2013
DOI: 10.1002/etc.2183
|View full text |Cite
|
Sign up to set email alerts
|

Sodium chloride enhances cadmium tolerance through reducing cadmium accumulation and increasing anti‐oxidative enzyme activity in tobacco

Abstract: The effect of sodium chloride (NaCl) on cadmium (Cd) uptake, translocation, and oxidative stress was investigated using 2 tobacco cultivars differing in Cd tolerance. The growth inhibition of the tobacco plants exposed to Cd toxicity was in part alleviated by moderate addition of NaCl in the culture solution. Cadmium concentration of shoots and roots in the 2 cultivars increased with increasing Cd levels in the solution and decreased with the addition of NaCl. The addition of NaCl could alleviate the oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 39 publications
4
11
0
1
Order By: Relevance
“…Phosphate suppresses As v uptake, which in turn constrains ROS production in cells. It has been reported previously that MDA content increases in plant cells under stress conditions [13,14,28,42]. These observations agree with the findings of the present study, in which exposing plants to 100 mM As v increased MDA content, whereas 500 mM PO 4 3decreased As content and resulted in low MDA content.…”
Section: Phosphate Effects On Arsenate Uptakesupporting
confidence: 93%
“…Phosphate suppresses As v uptake, which in turn constrains ROS production in cells. It has been reported previously that MDA content increases in plant cells under stress conditions [13,14,28,42]. These observations agree with the findings of the present study, in which exposing plants to 100 mM As v increased MDA content, whereas 500 mM PO 4 3decreased As content and resulted in low MDA content.…”
Section: Phosphate Effects On Arsenate Uptakesupporting
confidence: 93%
“…Also, H 2 O 2 can be converted into highly reactive hydroxyl radicals (OH · − ), which can cause lipid peroxidation . Studies have shown that CAT is the main H 2 O 2 ‐scavenging enzyme, which can eliminate H 2 O 2 by converting it to H 2 O and O 2 . The results of the present study showed that CAT activity was greatly stimulated by metalaxyl‐M exposure, which also suggested that earthworms suffered damage from metalaxyl‐M.…”
Section: Discussionsupporting
confidence: 59%
“…Although SOD can catalyze O 2 Á À to H 2 O 2 and O 2 , H 2 O 2 can also damage the cells. Also, H 2 O 2 can be converted into highly reactive hydroxyl radicals (OH Á À ), which can cause lipid peroxidation [21,22] [32,33]. The results of the present study showed that CAT activity was greatly stimulated by metalaxyl-M exposure, which also suggested that earthworms suffered damage from metalaxyl-M. Guaiacol peroxidase is another H 2 O 2 -scavenging enzyme, which also can prevent the formation of ROS [34].…”
Section: Discussionmentioning
confidence: 52%
“…4), confirming that salt addition reduced Cd translocation from root to shoot comparatively rapidly without influencing Cd uptake. Similar observations that NaCl decreased Cd root-to-shoot translocation in Nicotiana tabacum and the halophyte Kosteletzkya virginica have also been reported (Han et al, 2012;Zhang et al, 2013), although NaCl was proposed to enhance Cd translocation in plants through the formation of CdCl + , which is of increased mobility within plants (Clarke et al, 2002;Ozkutlu et al, 2007;Wali et al, 2015).…”
Section: Salinity Decreased CD Accumulation In Plant Shootssupporting
confidence: 72%